2022
DOI: 10.1002/jbio.202200062
|View full text |Cite
|
Sign up to set email alerts
|

Depth estimation of tumor invasion in early gastric cancer using scattering of circularly polarized light: Monte Carlo Simulation study

Abstract: Quantitative depth estimation of tumor invasion in early gastric cancer by scattering of circularly polarized light is computationally investigated using the Monte Carlo method. Using the optical parameters of the human stomach wall and its carcinoma, the intensity and circular polarization of light scattered from pseudo‐healthy and cancerous tissues were calculated over a wide spectral range. Large differences in the circular polarization with opposite signs, together with the large intensity, are obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Before proceeding to a potential practical application of the presented polarization helicity formalism (Section "A practical polarization metric deliverable"), we examine the details of subsurface propagation statistics for the flipped and preserved photons as afforded by the Monte Carlo simulation results. Though there have been previous studies on the behaviour of these photon types using numerical simulations 5,11,[14][15][16] , to the best of our knowledge this section represents the first such simulation-based investigation accompanied by corroborating experimental data to reinforce the validity of the results. Figure 6 displays a comparison of the simulation-obtained average number of scattering events N as a function of radial distance for the 1.04 μm spheres at µ s = 50 cm -1 (a) and µ s = 200 cm -1 (b).…”
Section: A Deeper Dive Into Polarization Statistics (Modeling Studies)mentioning
confidence: 63%
See 2 more Smart Citations
“…Before proceeding to a potential practical application of the presented polarization helicity formalism (Section "A practical polarization metric deliverable"), we examine the details of subsurface propagation statistics for the flipped and preserved photons as afforded by the Monte Carlo simulation results. Though there have been previous studies on the behaviour of these photon types using numerical simulations 5,11,[14][15][16] , to the best of our knowledge this section represents the first such simulation-based investigation accompanied by corroborating experimental data to reinforce the validity of the results. Figure 6 displays a comparison of the simulation-obtained average number of scattering events N as a function of radial distance for the 1.04 μm spheres at µ s = 50 cm -1 (a) and µ s = 200 cm -1 (b).…”
Section: A Deeper Dive Into Polarization Statistics (Modeling Studies)mentioning
confidence: 63%
“…It has also been observed that helicity flipping/preserving depends upon medium turbidity (quantified by the scattering coefficient) 12 , 13 —another scattering property whose alterations have been associated with malignancy 24 , 31 , 32 . Finally, circular polarization memory (i.e., ‘helicity survival’ 4 , 8 ) and ellipticity changes have shown importance for tumour detection 17 , 33 36 and depth estimation 15 . Thus, there are various ways in which helicity effects may potentially prove useful for noninvasive cancer-related diagnostics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…General observations of helicity sign changes have been reported in several studies, typically regarding the sign-change dependency on average scatterer size: flipping is favoured for smaller sizes and preservation is favoured for larger sizes [4,[8][9][10][11][12][13]. Further specific investigations of helicity effects are largely confined to numerical simulation results only [5,11,[14][15][16][17]. A complete experimental and theoretical (simulation) study of the helicity response would thus be desirable, to properly measure, understand, and quantify the sign, magnitude, and angular distribution of multiply-scattered circularly polarized light.…”
Section: Introductionmentioning
confidence: 89%
“…It has also been observed that helicity flipping/preserving depends upon medium turbidity (quantified by the scattering coefficient) [12,13] another scattering property whose alterations have been associated with malignancy [24,31,32]. Finally, circular polarization memory (i.e., 'helicity survival' [4,8]) and ellipticity changes have shown importance for tumour detection [17,[33][34][35][36] and depth estimation [15]. Thus, there are various ways in which helicity effects may potentially prove useful for noninvasive cancer-related diagnostics.…”
Section: Introductionmentioning
confidence: 99%